Output stabilization for infinite-dimensional bilinear systems - Zerrik, El Hassan; Ouzahra, Mohamed (Zielona Góra: Uniwersytet Zielonogórski)
The purpose of this paper is to extend results on regional internal stabilization for infinite bilinear systems to the case where the subregion of interest is a part of the boundary of the system evolution domain. Then we characterize either stabilizing control on a boundary part, or the one minimizing a given cost of performance. The obtained results are illustrated with numerical examples.
Keywords: infinite bilinear systems; output stabilization; regional stabilization